2019
DOI: 10.1016/j.kint.2019.03.033
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis indicates long-term risk of chronic and end-stage kidney disease after preeclampsia

Abstract: Preeclampsia is a pregnancy-related syndrome of variable severity, classically characterized by acute kidney involvement, with hypertension and/or proteinuria and reduced kidney function. Once considered a self-limited disease healed by delivery, it is now acknowledged that preeclampsia can affect cardiovascular and kidney health in the long term. The entity of risk has not been established and consequently follow-up policies have not been defined. Here we undertook a systematic review to gain better insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 84 publications
0
54
1
1
Order By: Relevance
“…It complicates 3%-5% of pregnancies worldwide [2], and affected women are at higher risk of long-term cardiovascular disease (CVD) [3][4][5]. Preeclampsia has also been described as a reversible kidney disease that typically self-resolves within 3 months of delivery [6]. However, there is increasing evidence that some women experience sustained renal dysfunction, and large cohort studies have reported an increased risk of end-stage kidney disease (ESKD) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It complicates 3%-5% of pregnancies worldwide [2], and affected women are at higher risk of long-term cardiovascular disease (CVD) [3][4][5]. Preeclampsia has also been described as a reversible kidney disease that typically self-resolves within 3 months of delivery [6]. However, there is increasing evidence that some women experience sustained renal dysfunction, and large cohort studies have reported an increased risk of end-stage kidney disease (ESKD) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Other changes in the renin-angiotensin-aldosterone system, metabolic system, and factors causing endothelial dysfunction may also be involved. Chronic kidney disease (CKD) is much more prevalent than ESKD, and although it may be considered a precursor to ESKD, the evidence for associations between preeclampsia and CKD has been inconsistent to date [6,14]. Cohort studies from Scotland and Denmark have reported increased risk of CKD following preeclampsia [15,16], but these findings have not been replicated elsewhere [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…
After decades in which the major medical textbooks reported with slightly different wordings that preeclampsia (PE) in pregnancy is a transitory kidney disease ultimately cured when the mother delivers, we are finally acknowledging that PE is neither always transitory nor systematically cured and that it may be both the herald of future diseases of the kidney and the cardiovascular system and the epiphenomenon of an underlying disease, as the interesting and well-presented case series published here demonstrates [1][2][3]. While the number of systematic reviews, large-population studies, and long-term registry data are multiplying and most of them conclude with a generic statement that future studies, actions, and programs are needed, few if any changes are taking place in real-life clinical practice [4].The result of this dangerous combination of minimalism (PE is a self-healing disorder), lack of interdisciplinary collaboration (the pragmatic obstetrician holding that "nephrologists make things too complicated," while the cultivated nephrologist retorts that "obstetricians oversimplify"), short-sightedness, and common alibis (no time to see all these women after a PE episode, someone else should do it …) is that women who have already had a stressful and occasionally life-threatening episode of PE lose a precious occasion to receive a timely diagnosis of a potentially curable disease.The series reported here is a clear example of how pregnancy is a valuable but often missed occasion for diagnosis of a potentially serious disease: of the 14 patients described, only 3 were diagnosed as having primary hyperaldosteronism within 1 year from the discovery of hypertension, while in 8 the interval was 5 years or more (up to 12 years).
…”
mentioning
confidence: 84%
“…After decades in which the major medical textbooks reported with slightly different wordings that preeclampsia (PE) in pregnancy is a transitory kidney disease ultimately cured when the mother delivers, we are finally acknowledging that PE is neither always transitory nor systematically cured and that it may be both the herald of future diseases of the kidney and the cardiovascular system and the epiphenomenon of an underlying disease, as the interesting and well-presented case series published here demonstrates [1][2][3]. While the number of systematic reviews, large-population studies, and long-term registry data are multiplying and most of them conclude with a generic statement that future studies, actions, and programs are needed, few if any changes are taking place in real-life clinical practice [4].…”
mentioning
confidence: 84%
“…6,7 On the other hand, a study that investigated proteinuria and renal function in former preeclamptic women 10 years after giving birth demonstrated only a high-normal estimated glomerular filtration rate and a slightly higher protein excretion. 8 To better assess the long-term renal risk of preeclampsia, Covella et al 9 performed a systematic review and a metaanalysis by selecting 21 papers, including 11 meta-analyses, published after 2000. Only papers reporting follow-ups of at least 4 years were selected.…”
mentioning
confidence: 99%